Streptococcus mitis Expressing Pneumococcal Serotype 1 Capsule. Issue 1 (December 2018) - Lessa, Fernanda; Milucky, Jennifer; Rouphael, Nadine; Bennett, Nancy; Talbot, H.; Harrison, Lee; Farley, Monica; Walston, Jeremy; Pimenta, Fabiana; Gertz, Robert; Rajam, Gowrisankar; Carvalho, Maria; et al.
Abstract Streptococcus pneumoniae's polysaccharide capsule is an important virulence factor; vaccine-induced immunity to specific capsular polysaccharide effectively prevents disease. Serotype 1S .pneumoniae is rarely found in healthy persons, but is highly invasive and a common cause of meningitis outbreaks and invasive disease outside of the United States. Here we show that genes for polysaccharide capsule similar to those expressed by pneumococci were commonly detected by polymerase chain reaction among upper respiratory tract samples from older US adults not carrying pneumococci. Serotype 1-specific genes were predominantly detected. In five oropharyngeal samples tested, serotype 1 gene belonging toS .mitis expressed capsules immunologically indistinct from pneumococcal capsules. Whole genome sequencing revealed three distinctS .mitis clones, each representing acps1 operon highly similar to the pneumococcalcps1 reference operon. These findings raise important questions about the contribution of commensal streptococci to natural immunity against pneumococci, a leading cause of mortality worldwide.